Comparison of Common Enrichment Broths Used in Diagnostic Laboratories for Shiga Toxin—Producing Escherichia coli - Michael Bording-Jorgensen; Hannah Tyrrell; Colin Lloyd; Linda Chui (Microorganisms, 2021)
Acute gastroenteritis caused by Shiga toxin-producing Escherichia coli (STEC) affects more than 4 million individuals in Canada. Diagnostic laboratories are shifting towards culture-independent diagnostic testing; however, recovery of STEC remains an important aspect of surveillance programs. The objective of this study was to compare common broth media used for the enrichment of STEC. Clinical isolates including O157:H7 as well as non-O157 serotypes were cultured in tryptic soy (TSB), MacConkey (Mac), and Gram-negative (GN) broths and growth was compared using culture on sheep’s blood agar and real-time PCR (qPCR). In addition, a selection of the same isolates was spiked into negative stool and enriched in the same three broths, which were then evaluated using culture on CHROMagarTM STEC agar and qPCR. TSB was found to provide the optimal enrichment for growth of isolates with and without stool. The results from this study suggest that diagnostic laboratories may benefit from enriching STEC samples in TSB as a first line enrichment instead of GN or Mac.